Intersectoriality as a managerial technology in Cuba voluntary blood donations - Pedro Sánchez Frenes; Vivian de las Mercedes Noriega Bravo (Medisur)
In Cuba there is wide experience in intersectoral work to solve health problems in the community and the management of blood donations is no exception. The objective of this work was to document the intersectoral work in the management of blood donations in Cuba and to provide theoretical elements that contribute to its improvement. A bibliographic review of the literature on intersectoriality and the processes for the management of blood donations in the country was carried out; For this, works published on Internet sites were consulted, as well as texts and other documents available in repositories of the Infomed web portal network. Intersectoriality is theorized and illustrated as a managerial technology and its use and importance applied in the promotion, capture and recruitment of potential donors and in the organization of blood collections. It is concluded that the use of intersectoriality in the health management of voluntary blood donations, strengthens and distinguishes the Cuban Blood Donation Program in relation to the rest of the world, however, it is necessary to improve the strategic alliances between the health sector and other sectors of organized civil society involved in the activities that comprise this process.